Exploring Islam from an American Perspective: A Study of the Views of McGill University Alumni in Indonesia - Anis Saidah; Firdah Ni’matus Sholihah; Iksan Iksan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to explore the dynamics of Islamic studies from a Western perspective, through the views of Indonesian alumni who have studied at McGill University, Canada. Using a qualitative approach and case study design, this research explores how cross-cultural academic experiences can shape a more critical, contextual, and interdisciplinary understanding of Islam. The main focus of this study is the paradigm shift in Islamic studies in the West, which was initially dominated by orientalism, towards a more open and dialogical scientific approach. Based on in-depth interviews with three McGill alumni who are actively involved in academics and religious activities in Indonesia, the findings suggest that McGill University plays a significant role in shaping reflective Islamic thought, adaptive to social realities, and supporting moderate values such as democracy, human rights, and pluralism. The implications of these findings are crucial for the development of Islamic studies in Indonesia, offering an approach that is more inclusive and relevant to Indonesia's social and cultural dynamics